2017
DOI: 10.7602/jmis.2017.20.4.129
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Consideration of Periappendiceal Abscess: an Evaluation of Non-surgical Treatment Followed by Minimally Invasive Interval Appendectomy

Abstract: Purpose: Periappendiceal abscess (PAA) is a severe complicated appendicitis with high morbidity. Non-surgical treatment followed by interval appendectomy (IA) is associated with lower complication rate compared with emergency surgery (ES) and minimally invasive surgery (MIS) can be done more often. The purpose of this study is to assess the incidence and factors predictive of complications of surgery for PAA and to evaluate the clinical effectiveness of IA as a treatment policy to increase MIS.Methods: Retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The incidence of interval appendectomy may be increased due to the increase in cases of complicated appendicitis resulting from delayed time from symptom onset to ER visit. According to previous studies, interval appendectomy was not inferior to the initial surgical approach in terms of reducing postoperative morbidity ( 16 , 32 ). Although the initial surgical approach was still preferred in South Korea, interval appendectomy increased as the proportion of complicated appendicitis cases increased during the pandemic.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The incidence of interval appendectomy may be increased due to the increase in cases of complicated appendicitis resulting from delayed time from symptom onset to ER visit. According to previous studies, interval appendectomy was not inferior to the initial surgical approach in terms of reducing postoperative morbidity ( 16 , 32 ). Although the initial surgical approach was still preferred in South Korea, interval appendectomy increased as the proportion of complicated appendicitis cases increased during the pandemic.…”
Section: Discussionmentioning
confidence: 71%
“…Emergency appendectomy is the treatment of choice, but there is still debate about its suitability in this pandemic era because several articles have reported that non-surgical management, such as antibiotic therapy, is non-inferior to appendectomy ( 14 , 15 ). In addition, it has been reported that initial non-surgical management, such as antibiotics, with or without percutaneous drainage followed by interval appendectomy in complicated cases such as periappendiceal abscess is effective and reduces postoperative complications compared to immediate appendectomy ( 16 ). Moreover, a change in the main treatment strategy has been observed in some countries.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of interval appendectomy may be increased due to the increase in cases of complicated appendicitis resulting from delayed time from symptom onset to ER visit. According to previous studies, interval appendectomy was not inferior to the initial surgical approach in terms of reducing postoperative morbidity [11,25]. Although the initial surgical approach was still preferred in South Korea, interval appendectomy increased as the proportion of complicated appendicitis cases increased during the pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…Emergency appendectomy is the treatment of choice, but there is still debate about its suitability in this pandemic era because several articles have reported that nonsurgical management, such as antibiotic therapy, is non-inferior to appendectomy [9,10]. In addition, it has been reported that initial non-surgical management, such as antibiotics, with or without percutaneous drainage followed by interval appendectomy in complicated cases such as periappendiceal abscess is effective and reduces postoperative complications compared to immediate appendectomy [11]. Moreover, a change in the main treatment strategy has been observed in some countries.…”
Section: Introductionmentioning
confidence: 99%